Pengaruh Penerapan Metode Kauny Quantum Memory Terhadap Peningkatan Tahsin Al-Qur’an Peserta Didik Kelas VII SMP Islam Terpadu Aminul Ummah Wanaraja Garut - Fauziah, Hapsah; Azizah, Nur (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
The process of memorizing the Qur'an can be expedited and enhanced through the study of Qur'anic recitation (tahsin), as tahsin encourages and enables students to read and memorize the Qur'an accurately. Students who struggle with reading, memorizing, and understanding the vocabulary of the Qur'an may find it challenging to apply tahsin. The Kauny Quantum Memory method is an approach designed to address students' difficulties in applying tahsin during Qur'anic memorization. The objectives of this research are: 1) to implement the Kauny Quantum Memory method for seventh-grade students at SMP IT Aminul Ummah; 2) to improve Qur'anic recitation skills (tahsin); 3) to assess the impact of the Kauny Quantum Memory method on the improvement of Qur'anic recitation skills among seventh-grade students at SMP IT Aminul Ummah. The research method used in this study is descriptive quantitative, involving the collection of data or information regarding the phenomenon under investigation. Data collection techniques include observation, literature review, questionnaires, and data processing through statistical analysis. The results indicate that the Kauny Quantum Memory method is classified as effective. Similarly, the improvement in Qur'anic recitation skills is also classified as effective. Statistical tests show that there is a significant influence between the Kauny Quantum Memory method and the improvement of Qur'anic recitation skills. Keywords: Kauny Quantum Memory Method, Improvement of Qur'anic Recitation